Impaired polyhydroxybutyrate biosynthesis from glucose in Pseudomonas sp. 14-3 is due to a defective β-ketothiolase gene - Ayub, Nicolás Daniel (2006)
Pseudomonas sp. 14-3 accumulates polyhydroxybutyrate (PHB) from octanoate, but not from glucose. To elucidate this unusual phenotype, genes responsible for the synthesis of PHB were cloned and analyzed. A PHB polymerase gene (phaC) was found downstream from genes coding for a β-ketothiolase (phaA), an acetoacetyl-coenzyme A reductase (phaB) and a putative transcriptional regulator (phaR). All genes were similar to pha genes from several related species, but differences were observed in the distal region of phaA. Complementation with heterologous β-ketothiolase genes from Azotobacter sp. FA8 or Pseudomonas putida GPp104 restored the capability of Pseudomonas sp. 14-3 to synthesize PHB from glucose, demonstrating that its β-ketothiolase was nonfunctional. Analysis of the genome sequences of other Pseudomonas species has revealed the existence of putative β-ketothiolase genes. The functionality of one of these thiolase genes, belonging to P. putida GPp104, was experimentally demonstrated. Pseudomonas sp. 14-3 is the first natural phaA mutant described, that despite this mutation accumulates high amounts of PHB when growing on fatty acids.